2021
DOI: 10.5194/hess-2021-566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrological Concept Formation inside Long Short-Term Memory (LSTM) networks

Abstract: Abstract. Neural networks have been shown to be extremely effective rainfall-runoff models, where the river discharge is predicted from meteorological inputs. However, the question remains, what have these models learned? Is it possible to extract information about the learned relationships that map inputs to outputs? And do these mappings represent known hydrological concepts? Small-scale experiments have demonstrated that the internal states of Long Short-Term Memory Networks (LSTMs), a particular neural net… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(55 reference statements)
0
11
0
1
Order By: Relevance
“…An analysis of state variables from the process models (not shown) confirms this is due to more precipitation as rain in the cold season, earlier snowmelt, and increased evapotranspiration triggered by warming. The CV-LSTM captures the same basic pattern despite not having explicit representations of these processes in its architecture; these processes are instead represented by the internal states of the network (Lees et al, 2021).…”
Section: Comparison Of Cv-lstm and Process-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of state variables from the process models (not shown) confirms this is due to more precipitation as rain in the cold season, earlier snowmelt, and increased evapotranspiration triggered by warming. The CV-LSTM captures the same basic pattern despite not having explicit representations of these processes in its architecture; these processes are instead represented by the internal states of the network (Lees et al, 2021).…”
Section: Comparison Of Cv-lstm and Process-based Modelsmentioning
confidence: 99%
“…Recent work has shown that LSTMs trained to hundreds of basins can predict extreme events with more accuracy than process models, even when the largest extremes are withheld during training (Frame, Kratzert, Klotz, et al, 2021). In addition, Lees et al (2021) showed that the cell states of globally trained LSTMs used to predict streamflow strongly correlated with latent hydrologic states, such as soil moisture storage and snowpack. These results suggest that DL hydrologic models are learning fundamental processes from the data, a concept further bolstered by the fact that LSTMs trained to many basins produce better out-of-sample streamflow predictions in a given basin than an LSTM only trained to that basin or a smaller subset (Gauch, Mai, & Lin, 2021;Kratzert, Klotz, Shalev, et al, 2019).…”
mentioning
confidence: 99%
“…For hydrologic modeling, it remains challenging to interpret what is being learned by LSTM, in part because it does not output physical states or fluxes. While it is possible to correlate LSTM's cell states to some physical states with regression approaches (Lees et al, 2021), the physical meaning of these cell states cannot be guaranteed explicitly, and we cannot run such regression tests before having access to the observations of those physical variables. The regression approach also does not allow us to freely ask questions about how the system functions.…”
mentioning
confidence: 99%
“…Also in the rainfall‐runoff domain, Kratzert et al (2019) used integrated gradients (Sundararajan et al, 2017) to confirm a theory‐consistent influence of precipitation and air temperature on a NN state that correlated with snow water equivalent, building trust in the ability of such models to capture known physical processes. More recent work on the same subject used probes (e.g., linear regression models or stacked multi‐layer perceptrons) to connect LSTM cell states to the output for tracking the evolution of the LSTM during the training process and verifying whether the LSTM learned physically realistic mappings from inputs to outputs (Lees et al, 2021).…”
Section: Opportunities For Advancement Of Water Quality MLmentioning
confidence: 99%